2013
DOI: 10.1007/s10195-013-0229-z
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary clinical experience with hyaluronan anti-adhesion gel in arthroscopic arthrolysis for posttraumatic elbow stiffness

Abstract: BackgroundLoss of motion of the elbow joint is a common finding after elbow trauma. It has been shown that arthroscopic treatment leads to excellent restoration of elbow motion, although it is still a demanding procedure. The aim of our cohort study was to assess clinical outcomes following treatment of posttraumatic elbow stiffness using arthroscopic arthrolysis with or without the associated use of a hyaluronan anti-adhesion gel.Materials and methodsA cohort of 36 consecutive patients undergoing elbow arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…A study using HA after arthroscopic arthrolysis of the elbow also showed no difference in recovery of motion between the injection and control groups. 36…”
Section: Discussionmentioning
confidence: 99%
“…A study using HA after arthroscopic arthrolysis of the elbow also showed no difference in recovery of motion between the injection and control groups. 36…”
Section: Discussionmentioning
confidence: 99%
“…Only two case series investigated HA in elbow osteoarthritis (Tab. IV) 96,97 . Level of recommendation: C.…”
Section: Elbow Osteoarthritismentioning
confidence: 99%
“…In osteoarthritis patients, synovial hyaluronate is depolymerized and is cleared at higher rates compared to normal subjects due to inflammation [ 12 ]. Intra-articular injections of hyaluronic acid have been shown to be as effective as NSAIDs with fewer systemic adverse events [ 13 ]; this therapy has a delayed onset of action in comparison with intra-articular corticosteroids, but a longer-lasting benefit [ 14 ]. Younger patients and patients at an earlier stage of the disease are more likely to benefit from viscosupplementation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%